2007
DOI: 10.1136/emj.2006.041293
|View full text |Cite
|
Sign up to set email alerts
|

How much do emergency healthcare workers know about capacity and consent?

Abstract: Aim: To assess knowledge of capacity and consent among emergency healthcare workers. Design: A cross-sectional survey with a structured questionnaire. Methods: 86 questionnaires were distributed and completed by 42 accident and emergency doctors, 21 accident and emergency nurses, and 23 emergency ambulance staff. Correct answers on assessing capacity to consent to or refuse treatment were given by 67% of the doctors and 10% of the nurses, but by none of the ambulance workers. 15% of all respondents wrongly bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 4 publications
3
35
0
Order By: Relevance
“…Seventy seven per cent of the asked re spondents answered the question correctly. The result is similar to the result of Evans et al, who observed that 90% of the doctors working in the medical emergency depart ment treat the patients illegally if they do not agree to such treatment [16]. Similarly, 90% of Evans's subjects gave the same answer and stated that the patient's family does not to have to give a consent or refusal if such cannot be ob tained from the patient.…”
Section: Discussionsupporting
confidence: 86%
“…Seventy seven per cent of the asked re spondents answered the question correctly. The result is similar to the result of Evans et al, who observed that 90% of the doctors working in the medical emergency depart ment treat the patients illegally if they do not agree to such treatment [16]. Similarly, 90% of Evans's subjects gave the same answer and stated that the patient's family does not to have to give a consent or refusal if such cannot be ob tained from the patient.…”
Section: Discussionsupporting
confidence: 86%
“…Previous surveys indicate that clinicians have limited understanding of the law pertaining to capacity. 6,7 Twenty-nine (81%) doctors in our survey indicated that they had received training about the Act, of which 23 (79%) felt that the training was adequate. Despite this, a startling and rather worrying revelation of our survey was that only seven (19%) respondents were aware of the exact criteria where 'unbefriended' incapacitous individuals must be referred to the IMCA service.…”
Section: Discussionmentioning
confidence: 91%
“…These difficulties include deficiencies in practitioner knowledge about the principles and legal responsibilities of the MCA. For example, a survey of 86 emergency care practitioners judged only 67% of doctors and 10% of nurses correct in their knowledge regarding capacity to consent or refuse treatment (Evans et al, 2007). Similarly, qualitative interviews with 32 care home staff found considerable variation in understanding of the terms and principles of the MCA (Manthorpe et al, 2011).…”
Section: Introductionmentioning
confidence: 99%